2010
DOI: 10.1152/ajpcell.00393.2009
|View full text |Cite
|
Sign up to set email alerts
|

Early transcription from the maternal genome controlling blastomere integrity in mouse two-cell-stage embryos

Abstract: Han Z, Mtango NR, Zhong Z, Vassena R, Latham KE. Early transcription from the maternal genome controlling blastomere integrity in mouse two-cell-stage embryos. Am J Physiol Cell Physiol 298: C1235-C1244, 2010. First published January 27, 2010 doi:10.1152/ajpcell.00393.2009Blastomere cytofragmentation in mammalian embryos poses a significant problem in applied and clinical embryology. Mouse two-cell-stage embryos display strain-dependent differences in the rate of cytofragmentation, with a high rate observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Aside from apoptosis, the disruption of the correct control of the contractile apparatus/actin metabolism can represent an alternative mechanism of fragmentation directly exerted on the cytoskeleton 35 . Beyond the ooplasmic or genetic origin of embrionic fragmentation, it has been showed that fragmentation may reflect cellular responses to suboptimal culture conditions [36][37][38][39] and, of note, this propensity is programmed very early, at the one-cell stage 40,41 . Our experimental model, although not designed to explore the mechanisms of cell death or fragmentation, supports the hypothesis that environmental factors in the very early stages of development can modulate the predisposition of an oocyte to arrest by cytofragmentation after fertilization with an exclusive effect on the maternal cellular armamentarium.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from apoptosis, the disruption of the correct control of the contractile apparatus/actin metabolism can represent an alternative mechanism of fragmentation directly exerted on the cytoskeleton 35 . Beyond the ooplasmic or genetic origin of embrionic fragmentation, it has been showed that fragmentation may reflect cellular responses to suboptimal culture conditions [36][37][38][39] and, of note, this propensity is programmed very early, at the one-cell stage 40,41 . Our experimental model, although not designed to explore the mechanisms of cell death or fragmentation, supports the hypothesis that environmental factors in the very early stages of development can modulate the predisposition of an oocyte to arrest by cytofragmentation after fertilization with an exclusive effect on the maternal cellular armamentarium.…”
Section: Discussionmentioning
confidence: 99%
“…Although not many studies have been published so far, our observations are in agreement with the results of previous studies. Even with different detection methods, damaging effects of CP procedures (SF and VF) on embryo chromatin integrity and function have been reported [ 34 , 54 , 55 ]. Isachenko et al [ 21 ] found that the nuclear chromatin integrity rate after CP of pronuclear zygotes was a predictor of future embryo development and implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Embryo fragmentation is clinically considered as an indicator of reduced embryo viability and developmental ability, reduced number of high quality embryos available for establishing pregnancies, thus as a relevant problem for assisted reproduction outcome. In fresh embryos, blastomere fragmentation has been reported to be associated to apoptosis [24,35,36] or to apoptosis and necrosis [37]. A recent study [36] revealed novel early transcription mechanisms by which maternal genotype affects cytofragmentation by alterating regular cytoskeletal functions.…”
Section: Discussionmentioning
confidence: 99%
“…In fresh embryos, blastomere fragmentation has been reported to be associated to apoptosis [24,35,36] or to apoptosis and necrosis [37]. A recent study [36] revealed novel early transcription mechanisms by which maternal genotype affects cytofragmentation by alterating regular cytoskeletal functions. In the present study, in which embryos were examined no more than two hours after warming (including staining procedures), these mechanisms could be only hypothesized.…”
Section: Discussionmentioning
confidence: 99%